Respuesta :

the answer is √x + √y = √c 
=> 1/(2√x) + 1/(2√y) dy/dx = 0 
=> dy/dx = - √y/√x 

Let (x', y') be any point on the curve 
=> equation of the tangent at that point is 
y - y' = - (√y'/√x') (x - x') 

x-intercept of this tangent is obtained by plugging y = 0 
=> 0 - y' = - (√y'/√x') (x - x') 
=> x = √(x'y') + x' 

y-intercept of the tangent is obtained by plugging x = 0 
=> y - y' = - (√y'/√x') (0 - x') 
=> y = y' + √(x'y') 

Sum of the x and y intercepts 
= √(x'y') + x' + y' + √(x'y') 
= (√x' + √y')^2 
= (√c)^2 (because (x', y') is on the curve => √x' + √y' = √c) 
= c.  hope this helps :D